A family of estimators of finite population mean with dual use of auxiliary information in sample surveys - Nigam, Dr. Pragati; Prasad Singh, Housila (Brazilian Journal of Biometrics, 2026)
In this paper we have suggested a family of estimators for estimating the population mean of the study variable with the dual use of auxiliary information in sample surveys. In addition to Haq et al. (2017) many other estimators are members of the proposed family of estimators. The bias and mean squared error of the suggested family of estimators are obtained up to the first order of approximation. We have compared the proposed family of estimators with some existing estimators and derived the conditions under which the suggested family of estimators is more efficient than the existing estimators. An empirical study is carried out to demonstrate the performance of the proposed family of estimators over existing estimators.